Rehabilitation of Visual Loss: Where We Are and Where We Need to Be. Issue 2 (June 2018) - Mansouri, Behzad; Roznik, Marinya; Rizzo, Joseph F.; Prasad, Sashank
Abstract : Background: Spontaneous recovery of visual loss resulting from injury to the brain is variable. A variety of traditional rehabilitative strategies, including the use of prisms or compensatory saccadic eye movements, have been used successfully to improve visual function and quality-of-life for patients with homonymous hemianopia. More recently, repetitive visual stimulation of the blind area has been reported to be of benefit in expanding the field of vision. Evidence Acquisition: We performed a literature review with main focus on clinical studies spanning from 1963 to 2016, including 52 peer-reviewed articles, relevant cross-referenced citations, editorials, and reviews. Results: Repetitive visual stimulation is reported to expand the visual field, although the interpretation of results is confounded by a variety of methodological factors and conflicting outcomes from different research groups. Many studies used subjective assessments of vision and did not include a sufficient number of subjects or controls. Conclusions: The available clinical evidence does not strongly support claims of visual restoration using repetitive visual stimulation beyond the time that spontaneous visual recovery might occur. This lack of firm supportive evidence does not preclude the potential of real benefit demonstrated in laboratories. Additional well-designed clinical studies with adequate controls and methods to record ocular fixation are needed. Abstract : Supplemental Digital Content is Available in the Text.